Development of Learning Modules and Interactive Digital Content to Increase Student Interest and Learning Motivation at SMA Kallista Batam - Lady, Lady; Cristina, Cristina (Lembaga Penelitian dan Pendidikan Mandala, 2025)
This study aims to address the issue of low student interest and motivation at Kallista Batam School, caused by the monotonous conventional teaching methods and limited interaction between teachers and students. The one-way teaching approach, which does not actively involve students in the learning process, leads to a lack of concentration and enthusiasm in participating in lessons. As a solution, the author developed interactive digital learning modules using PowerPoint, quizzes, and application-based learning media to enhance student engagement in the learning process. The methods used in this study are the Diffusion of Science and Technology (Iptek) and Substitution of Iptek, which aim to integrate educational technology into teaching to improve student understanding and motivation. The results show that the use of interactive digital learning media successfully created a more engaging and enjoyable learning environment, while encouraging students to actively participate in discussions and quizzes. Based on these findings, it is recommended that similar programs be implemented more widely in schools by providing teacher training in utilizing technology and introducing more interactive tools and applications for learning.